Gestão participativa no SUS e a integração ensino, serviço e comunidade: a experiência da Liga de Saúde da Família, Fortaleza, CE Participatory management in SUS through integrating education, and community service: the experience of a family health league as a project of University extension in Fortaleza - Ceará - Ivana Cristina de Holanda Cunha Barreto; Luiz Odorico Monteiro de Andrade; Ana Ester Maria Melo Moreira; Márcia Maria Tavares Machado; Maria Rocineide Ferreira da Silva; Lúcia Conde de Oliveira; Walda Viana Brígido Moura; Cezar Wagner de Lima Góis; Caio Garcia Correia Sá Cavalcanti; Maria Marlene Marques Ávila; Maria Fátima Maciel Araujo; Lucilane Maria Sales da Silva; et al. (Universidade de São Paulo, 2012)
Fruto da experiência de duas universidades públicas e uma privada, o Projeto de Extensão Liga Saúde da Família (LSF) constitui-se numa estratégia de gestão participativa no campo da formação de profissionais da área da saúde, com base nos conceitos de educação permanente em saúde, educação popular em saúde, equipe multiprofissional e interdisciplinar, atenção primária à saúde, promoção da saúde, estratégia saúde da família, metodologias participativas de pesquisa e atuação inserida no território vivo. Este relato apresenta a experiência da integração ensino-serviço-comunidade por meio do Projeto de Extensão Liga Saúde da Família, no contexto do Sistema Municipal de Saúde Escola (SMSE), em Fortaleza-Ceará, que dialoga com a gestão participativa no Sistema Único de Saúde (SUS). Esta proposta do LSF foi implantada no SMSE a partir de uma ação apoiada pelo sistema de saúde de Fortaleza que visa potencializar os espaços de co-gestão docente-assistencial, por meio da proposta do método da roda e da tenda invertida. O protagonismo dos integrantes e da comunidade na construção das atividades do projeto e a ampliação do olhar crítico sobre a realidade social e do trabalho em saúde estão entre os maiores avanços surgidos dessa experiência. Esse projeto permitiu a integração ensino - serviço - comunidade, atendendo a uma perspectiva de gestão participativa e dialógica. As a result of the experience of two public universities and a private one, the Extension Project "Family Health League" (LSF) introduced a participative management strategy in the field of education of health professionals, with the support of power-ideas such as permanent education in health, popular education, multiprofessional and interdisciplinary groups, primary health attention, family health strategy, participative methodologies and practice inserted in a live territory. This report aims to introduce an experience of integrating teaching to community service through the Family Health League Extension Project (LSF), in the context of the Health-School Municipal System (SMSE) in the city of Fortaleza, Ceará, Brazil. This experience was planned in the spirit of participative management in the National Health System (SUS). The proposal of LSF emerges, in the SMSE, from a recommendation supported by the city's health system which aimed at improving co-management spaces of education and services and used the methods of circle discussion and inverted tent. The protagonism of the project members and of the community in the organization of the project's activities and the amplification of a critical view over social reality and health work are amongst the major advances which emerged from this experience. This project has made possible the integration of teaching, health service and community, from the perspective of a communicative and participative management.